Extraction of glycoside compound from Salicorinia europeae L. and evaluation of its chemical properties and antibacterial activity - Sabaa Ali (University of Thi-Qar Journal of Science, 2019)
Saponin glycoside compound isolated from Salicorinia europeae L.(Salicornioideae:Chenopodiaceae), that proved by using specific test (haemolysis test,foam test and libermann bruchard test).TLC was used to detect the purity of this compound which give one spot,also IR-spectrum,UV-spectrum,Meltingpoint,solubility were also used to detect the chemical properties of this compound.The antibacterial activityof extracted glycoside was examined against two clinical isolates[Escherichia coli and Staphylococcusaureus] using disk diffusion method.Cork Poorer method was used to determine the minimum inhibitoryconcentration (MIC) for the extracted glycoside.The study showed that the MIC values of the compound was35,35,55 V/V% ,against clinical isolates Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosaespectively.